Natural distribution of the genus Dacrydium Lamb. (Podocarpaceae) in Central Kalimantan, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Maimunah S, Kessler PJA, Indrioko S, Naiem M. 2022. Natural distribution of the genus Dacrydium Lamb. (Podocarpaceae) in Central Kalimantan, Indonesia. Biodiversitas 23: 2816-2822. The tropical coniferous genus Dacrydium is widespread in Kalimantan, Indonesia. It is estimated that four species still exist in Borneo, locally known as Alau. This genus thrives in a range of habitats, from heath to deep-peat forests in Central Kalimantan. This genus is currently threatened by logging, fire, and forest conversion to plantations. The objectives of this study were: 1) to know the distribution and abundance of Dacrydium, and 2) to describe the Dacrydium’s habitat. The research was conducted in a heath forest located in PT Taiyoung Engreen (PTTE) in Gunung Mas District and PT Dasa Intiga (PTDI) in Kapuas and North Barito District, and in deep-peat swamp forest located in Sebangau National Park (SNP) in Palangka Raya and Pulang Pisau District. Data were collected in plots, each measuring 50 x 80 m, and the collected data were analyzed using a biodiversity calculator device created by MSU in USAID Lestari 2019. The identified specimens of alau found were sent to Herbarium Bogoriense for validation. The results of the analysis showed that we could identify three species of alau from the four species that are suspected to exist in Kalimantan. namely Dacrydium beccarii Parl. (alau bakam (B)); Dacrydium pectinatum de Laub. (alau kelangkang (K)), and Dacrydium elatum (Roxb.) Wall. ex Hook. (alau tombak (T)) with various abundance. Depending on the conditions of habitat, Alau could be found only in some parts of heath to deep-peat swamp forest. The finding of D. pectinatum in the study areas is a new discovery because it was previously reported that this species was not found in Central Kalimantan.